Stat5b Regulates Sexually Dimorphic Gene Expression in Zebrafish Liver - Huang, Peipei; Xiong, Shuting; Kang, Jingliang; Mei, Jie; Gui, Jian-Fang (Frontiers in Physiology, 2018)
Sexual size dimorphism is an interesting phenomenon occurred in many fish species. Wildtype zebrafish exhibits a significant sexual dimorphism in body size at the adult stage. Previous studies indicated that sexual size dimorphism was eliminated in stat5b-mutated zebrafish. Herein, the comparative transcriptome analysis was conducted to observe the genes and pathways involved in sexual size dimorphism. The number of male-biased and female-biased genes was much less in the liver of stat5b mutant zebrafish than in wildtype. Gene ontology (GO) enrichment and Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis indicated that multiple pathways related to metabolism were affected upon loss of stat5b function. qRT-PCR results also validated that sexually dimorphic expression of a set of genes was lost when stat5b was mutated. Furthermore, the weighted correlation network analysis (WGCNA) detected many candidate genes related to the growth traits and stat5b function, such as greb1, lepr and igf2b. Our data suggest that stat5b should regulate the sexually dimorphic gene expression in zebrafish liver and add in understanding of the molecular mechanisms underlying sexual size dimorphism in fish species.